2021
DOI: 10.1080/15332748.2021.1951022
|View full text |Cite
|
Sign up to set email alerts
|

The Archives at the Tip of Their Fingers: Exploring User Reactions to Large-Scale Digitization

Abstract: Advances in digital image capture technology and the adoption of More Product, Less Process methods have resulted in special collections and archives large-scale digitization that creates a new kind of digital surrogate. Mirroring and reusing aggregate archival arrangement and description, these digital surrogates represent multiple items and are minimally described as a whole. The authors conducted interviews to explore user reactions to this digitization method at the University of Nevada, Las Vegas. This st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…In accordance with the Thematic Map, it was possible to delimit the 10 fields where digitization is most often applied, and these are shown in Table 2. Regarding the digitization of files as a process of conversion from analog to digital format, there is an investigation called "The Archives at the Tip of Their Fingers: Exploring User Reactions to Large-Scale Digitization" prepared by [35], who conducted several interviews in order to analyze the responses of users of the digitization method "More Product, Less Process" at the University of Nevada, Las Vegas. The study found that digitization at a large-scale level positively impacted users; however, other strategies may be needed to make the most of the associated digital objects.…”
Section: Fields Where Digitization Is Appliedmentioning
confidence: 99%
“…In accordance with the Thematic Map, it was possible to delimit the 10 fields where digitization is most often applied, and these are shown in Table 2. Regarding the digitization of files as a process of conversion from analog to digital format, there is an investigation called "The Archives at the Tip of Their Fingers: Exploring User Reactions to Large-Scale Digitization" prepared by [35], who conducted several interviews in order to analyze the responses of users of the digitization method "More Product, Less Process" at the University of Nevada, Las Vegas. The study found that digitization at a large-scale level positively impacted users; however, other strategies may be needed to make the most of the associated digital objects.…”
Section: Fields Where Digitization Is Appliedmentioning
confidence: 99%